Educação especial no ensino superior : processos sociais comparados entre México e Brasil - Conceição, Júnio Hora (2017)
The text has the purpose to analyze processes triggered by the public policies of admission and, especially, of permanence, for students targeted by Special Education in Higher Education, in a Latin American context, focusing on the comparative study between Mexico and Brazil. We emphasize the period from 1996 to 2016 as a temporal cut, the last two decades, marked by educational reforms in both countries. Methodologically, we did a historical-documentary study of the legislations that marked the public policies in the period highlighted, as well as statistical data related to the enrollment flow of the target public students of Special Education in Higher Education. We also sought to analyze the tensions experienced by different individuals and groups in the Social Processes of two university contexts: Universidad Veracruzana (Mexico) and Federal University of Espírito Santo (Brazil). From the oral interviews of students from both universities, we have analyzed the possibilities and challenges experienced in everyday university life. The theoretical background perspective is based on Social Processes Theory elaborated by Norbert Elias (1993, 1998a, 2001, 2006 and 2011). In a long-running historical flow, Elias analyzes the Civilizing Processes emphasizing that societies are constituted in the set of relations between individuals and social groups, whose processes of interdependence form human figurations. They experience the historical transformations in the different interdependent societies. The research data show that the effective participation of students targeted by Special Education, although sometimes fragile, have a preponderant force in the balance of power for the implementation of public policies in the studied universities. At the same time, the mexican and brazilian Etates failed to offer concrete conditions to break this fragility, and to ensure to the Special Education a stable place in Higher Education. Nevertheless, Social Processes contribute to the continuing flow of the Civilizing Process of Western societies.